The Digital Rights Movement : The Role of Technology in Subverting Digital Copyright - Postigo, Hector (Book collections on Project MUSE., 2012)
The evolution of activism against the expansion of copyright in the digital domain, with case studies of resistance including eBook and iTunes hacks.